Tuning Fluorination of Linear Carbonate for Lithium-Ion Batteries. Issue 4 (1st April 2022) - Yu, Zhiao; Yu, Weilai; Chen, Yuelang; Mondonico, Luca; Xiao, Xin; Zheng, Yu; Liu, Fang; Hung, Samantha T.; Cui, Yi; Bao, Zhenan
Abstract : Liquid electrolyte engineering plays a critical role in modern lithium-ion batteries. However, the existing electrolytes fall short when used with some trending battery chemistries such as high-voltage and high-energy-density electrodes. Fluorination of electrolyte solvents has been identified as an effective approach for improved cyclability, but few works systematically studied the effects of fluorination extent of carbonate solvents on battery performance. Here we design and synthesize a family of fluorinated ethyl methyl carbonates. Different numbers of F atoms are finely tuned to yield monofluoroethyl methyl carbonate (F1EMC), difluoroethyl methyl carbonate (F2EMC) and trifluoroethyl methyl carbonate (F3EMC). The cycling behavior of several types of lithium-ion pouch cells, including graphite (Gr)/single-crystalline LiNi0.8 Mn0.1 Co0.1 O2 (SC-NMC811), Gr-SiOx /LiNi0.6 Mn0.2 Co0.2 O2 (NMC622), high-voltage Gr/LiNi0.5 Mn1.5 O4 (LNMO), Gr/layered Li-rich Mn-based oxide (LLMO) and fast-charging Gr/NMC622, were systematically investigated to understand the impact of fluorination degree. Compared to the commercially available F3EMC, we found that the partially-fluorinated F1EMC and F2EMC in some cases showed improved cycling stability, which we attribute to their locally-polar –CH2 F and –CHF2 groups and thus fast ion conduction than –CF3 . This work suggests that highly or fully fluorinated solvents are not necessarily desirable; instead, fluorination degree needs to be rationally and finely tuned for optimized lithium-ion cell performance.